Modelling of Locomotive Normal Load - Nikšić, Mladen; Kaužljar, Dražen; Magličić, Denis (Promet - Traffic&Transportation)
The paper deals with two topics. The one is strictly railways,that is theoretical theses for calculation of locomotive load atrespective gradient. The second is an overview of computer programMS Access with the basic terms and definitions includedin the program itself It is intended to bring closer the languageof information technology to the railways. The developed programfor calculating the allowed mass of trains that can behauled by certain locomotives enables fast calculation of any ofthe traction variants. A limitation related to mass has been includedin the program.